Transverse myelitis as an unexpected complication following treatment with dinutuximab in pediatric patients with high‐risk neuroblastoma: A case series. Issue 1 (27th July 2017) - Ding, Yang‐Yang; Panzer, Jessica; Maris, John M; Castañeda, Alicia; Gomez‐Chiari, Marta; Mora, Jaume
Abstract: Immunotherapy with the anti‐GD2 monoclonal antibody ch14.18, or dinutuximab, represents an important therapeutic advance in the treatment of pediatric high‐risk neuroblastoma and is now considered part of standard of care in this patient population. To date, transverse myelitis as a result of dinutuximab therapy has not been reported in clinical trials or in the published literature. We describe three patients with clinical symptoms of transverse myelitis, confirmed via magnetic resonance imaging, shortly following initiation of dinutuximab. All patients were discontinued from dinutuximab treatment and received urgent treatment, with rapid improvement in symptoms and resultant functional recovery.